Population dynamics of reintroduced Gunnison's Prairie dogs in the southern portion of their range. Issue 3 (10th March 2014) - Davidson, Ana D.; Friggens, Michael T.; Shoemaker, Kevin T.; Hayes, Charles L.; Erz, Jon; Duran, Ricardo
ABSTRACT Burrowing, herbivorous mammals play important roles as ecosystem engineers and keystone species of grassland ecosystems around the world, but populations of many species have declined dramatically because of myriad threats from human activities. Prairie dogs (Cynomys spp.) play important roles in shaping the central grasslands of North America, and have declined by about 98% across their range, with consequent losses in associated species and grassland habitat. This has prompted much interest in restoring their populations to protected areas. Managers lack a clear understanding of the long‐term success of reintroductions, however, and how success may vary across different species of prairie dogs and their widespread geographic ranges. We reintroduced over 1, 000 Gunnison's prairie dogs (C. gunnisoni) to a semi‐arid grassland ecosystem in the southern portion of their range in central New Mexico, USA, and used standard capture–recapture methods to study their population dynamics over a period of 8 years. Mean adult survival was 27% over the course of the study, with precipitation identified as the primary driver of survival. Estimated survival was below 12% during severe drought periods and during the first few years following initial reintroduction, the latter likely because of high predation. Consequently, multiple releases of animals were required to prevent extirpation, and the long‐term sustainability of this population remains questionable. Over the 8 years of our study, our site experienced 4 severe droughts during spring, the key period for prairie dog mating, pregnancy, and lactation. Production of offspring at the site was low, likely because of the dry and variable conditions that occurred. We show that prairie dog restoration in semi‐arid grassland environments that are typical of the lower elevations and southern extent of their range may not succeed in producing viable colonies, and that dedicated management for multiple years is needed to counteract periods of slow or negative population growth. Our findings underscore the importance of maintaining and expanding existing colonies wherever possible in these more arid regions, and suggest that reintroductions should be treated as a secondary management strategy. Our work also reveals the high vulnerability of prairie dog population extinction due to drought, which has important implications for Gunnison's prairie dog conservation under a warming and drying climate. © 2014 The Wildlife Society.